Study of Spectrum of Rheumatic Diseases in the Department of Physical Medicine & Rehabilitation, Chittagong Medical College Hospital, Bangladesh - Al Hasan, Suzon; Rahim, Md Abdur; Siddiq, M Abu Bakar; Hossain, Md Shawkat; Taslim, Abu; Paul, Sujat; Barua, Anupam; Hassan, Md Mahtab Uddin; Islam, Md Nazrul; Haq, Syed Atiqul (Journal of Chittagong Medical College Teachers' Association, 2010)
Key words: rheumatic disorder; spectrum; teaching hospital DOI: 10.3329/jcmcta.v20i1.4927 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):6-11